Analysis of Airflow in Corridors, Staircases, and Voids using Exhaust Fans - Sahabuddin Latif (Jurnal Arsitektur, 2023)
The existence of corridors, stairs and void spaces is often overlooked in terms of thermal comfort, especially in buildings that are large and have many floors. This study aims to investigate the performance of exhaust fans in ventilating air out of the building to address heat issues in corridors, staircases, and void spaces, using a case study of the Classroom Building in the Engineering Faculty of Unhas Gowa Campus. The method employed in this study involved computer simulations using Solid Work Flow Simulation software. The simulation scenarios consisted of four types, with variations in volume flow, opening types, and fan placement. The results of the study indicate that the exhaust fan system is considered less effective in ventilating air out of the building due to the presence of long corridors, large void spaces, and environmental opening systems, resulting in only the areas near the exhaust fan having significant airflows. Furthermore, the air stacking effect that occurs in the void, directing air upwards towards the roof ventilation, also leads to a less effective performance of the exhaust fan.